Effect of toxic metals on oral tissues - Katarzyna Herman; Mariusz Korczyński; Maciej Janeczek; Paweł Wełmiński; Małgorzata Kowalczyk-Zając; Anna Leśków; Ireneusz Całkosiński; Maciej Dobrzyński (Kazimierz Wielki University, 2017)
Toxic metals that commonly occur in human environment may exert a negative influence on people's health. This study presents the problem of pathological changes occurring within the oral cavity as a result of exposure to toxic metals. According to literature, they may adversely affect soft tissues, teeth, the saliva secretion process or taste sensations. There is also risk of developmental defects of the facial skeleton, particularly the cleft palate and impaired tooth buds mineralization. Therefore, it is essential to limit industrial and non-industrial sources of toxic metals.